Phenotypic Switching of Staphylococcus aureus Mu50 Into a Large Colony Variant Enhances Heritable Resistance Against β-Lactam Antibiotics - Sun, Yajun; Liu, Miaomiao; Niu, Mingze; Zhao, Xin (Frontiers in Microbiology, 2021)
Phenotypic heterogeneity within a bacterial population may confer new functionality and allow microorganisms to adapt to fluctuating environments. Previous work has suggested that S. aureus could form small colony variants to avoid elimination by therapeutic antibiotics and host immunity systems. Here we show that reversible large colony morphology (Mu50∆lcpA-LC) was observed in S. aureus Mu50 after knocking out lcpA, coding for the LytR-CpsA-Psr family A protein. Mu50∆lcpA-LC increased resistance to β-lactam antibiotics. In addition, enhanced spreading ability on solid medium and reduced biofilm formation, suggesting better abilities for spreading the infection. Moreover, expression of a spa gene, encoding the protein A that is responsible for evasion of immunity, was significantly increased in Mu50∆lcpA-LC. This study shows that besides the small colony variants, S. aureus could fight against antibiotics and host immunity through phenotype switching into a large colony variant.